2018
DOI: 10.1177/2515690x18794158
|View full text |Cite
|
Sign up to set email alerts
|

Cellulite Reduction by Modified Thai Herbal Compresses; A Randomized Double-Blind Trial

Abstract: Cellulite remains an obstinate clinical and cosmetic problem. In this study, we adapted the Thai traditional noninvasive treatment formulated with 5 additional herbals to improve blood flow, edema, and lipolysis, thereby augmenting cellulite treatment. This was a double-blind, randomized placebo-controlled paired trial. Twenty-one women (20-55 years) having cellulite (grade ≥2) were treated with steamed placebo or herbal compresses randomly assigned to one or other thigh twice weekly for 8 weeks with 2 weeks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
(39 reference statements)
4
12
0
2
Order By: Relevance
“…Our previous clinical study showed that the anti-cellulite herbal compress improved cellulite appearance, as assessed by measurement of thigh circumferences, skin thickness and severity of cellulite [ 7 ]. Blood flow enhancement via vasodilation could be one of the mechanisms activated by the anti-cellulite herbal compress.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous clinical study showed that the anti-cellulite herbal compress improved cellulite appearance, as assessed by measurement of thigh circumferences, skin thickness and severity of cellulite [ 7 ]. Blood flow enhancement via vasodilation could be one of the mechanisms activated by the anti-cellulite herbal compress.…”
Section: Resultsmentioning
confidence: 99%
“…The vascular action of the herbal compress could be attributed to some of the major constituents of mixed oil, in particular monoterpenes i.e., α-pinene, camphene, β-pinene, β-myrcene, 3-carene, D-limonene, camphor, terpinene-4-ol β-citral and α-citral, which were displayed on chromatographic profiles shown in a GC-MS chromatogram ( Figure 6 ). The mechanism of vasorelaxant actions of the mixed oil could involve the endothelium dependent pathway i.e., nitric oxide release, as reported by several studies evaluating vascular actions of the volatile oils and plants containing similar monoterpene profiles [ 7 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 45 One study assessing durability noted that cellulite severity improvements were short term (<2 weeks). 17 A sugar derivative, sulfocarrabiose, reduced lipogenesis and increased lipolysis in vitro, and a randomized trial of 25 women applying a 3% sulfocarrabiose cream twice per day on the thigh for 8 weeks noted improvement in cellulite severity using a numeric scale (range: 0, no cellulite to 10, maximum cellulite; p < .05). 21 …”
Section: Treatment Of Cellulitementioning
confidence: 99%